Predicting Forefoot-Orthosis Interactions in Rheumatoid Arthritis Using Computational Modelling - Kelly, Emily S.; Worsley, Peter R.; Bowen, Catherine J.; Cherry, Lindsey S.; Keenan, Bethany E.; Edwards, Christopher J.; O’Brien, Neil; King, Leonard; Dickinson, Alex S. (Frontiers in Bioengineering and Biotechnology, 2021)
Foot orthoses are prescribed to reduce forefoot plantar pressures and pain in people with rheumatoid arthritis. Computational modelling can assess how the orthoses affect internal tissue stresses, but previous studies have focused on a single healthy individual. This study aimed to ascertain whether simplified forefoot models of people with rheumatoid arthritis of varying severity produced differing biomechanical predictions from each other and from a healthy control, for the future purpose of aiding orthosis design. The forefoot models were developed from MR data of 13 participants with rheumatoid arthritis and 1 healthy individual. Measurements of bony morphology and soft tissue thickness were taken to assess deformity. These were compared to model predictions (99th% shear strain and plantar pressure, max. pressure gradient, volume of soft tissue over 10% shear strain), alongside clinical data including BMI and Leeds Foot Impact Scale– Impairment/Footwear score (LFIS-IF). The predicted pressure and shear strain for the healthy participant fell at the lower end of the rheumatoid models’ range. Medial 1st metatarsal head curvature moderately correlated to all model predicted outcomes (0.529